The Effect of PMSE Tax Policy, Tax Socialization, and Taxpayer Compliance on State Tax Revenue (A Study of E-Commerce Players in Jakarta) - Pamela Colleen; Nurul Hidayah (Universitas Mercu Buana, 2024)
This research was conducted to determine the influence of PMSE tax policy, tax socialization, and taxpayer compliance on state tax revenue, with a study on e-commerce actors in Jakarta. This research uses a quantitative approach. The analysis methods used are PLS-SEM analysis and Logistic Regression using SmartPLS 3.0 software. Based on the research results, the study shows that the PMSE tax policy variable has a negative and insignificant effect on state tax revenue. The tax socialization and taxpayer compliance variables have a positive and significant effect on state tax revenue.